Penyelesaian Sengketa Merek Pstore Glow dan MS GLOW Menurut Asas First To File - Clements Laso Jati; Hernawan Hadi (Universitas Sains dan Teknologi Komputer, 2024)
This article discusses the dispute resolution undertaken by Shandy Purnamasari and Putra Siregar related to their Brand disputes, namely MS GLOW and PSGlow which will be reviewed based on the principle of fisrt to File and Law Number 20 of 2016 concerning Marks and Geographical Indications. This type of legal research is perscriptive normative legal research with secondary data types including primary and secondary legal materials. The technique of collecting legal materials is carried out with literature, then used The analysis technique used is the deductive method. This study produces the author's views on dispute resolution which is reviewed on the principle of First to File.